2009
DOI: 10.1002/pd.2344
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression in chorionic villous samples at 11 weeks of gestation in women who develop preeclampsia later in pregnancy: implications for screening

Abstract: CVS show an aberrant gene profile prior to preeclampsia onset that may be predictive of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…25 Previous studies have reported that it is possible to assess gene expression differences in first trimester placentae from pregnancies with known outcomes, well before clinical disease symptoms or developmental abnormalities are apparent. [26][27][28][29][30][31][32] The results of this study correlate with our previous findings in which we have demonstrated a significant reduction in placental BGN from human pregnancies complicated by FGR collected at third trimester gestation compared with gestation-matched controls. 18 The results from this study support a temporal relationship between reduced BGN expression and SGA/FGR and, therefore, suggest a causal role for placental BGN in the success of pregnancy outcome.…”
Section: Discussionsupporting
confidence: 81%
“…25 Previous studies have reported that it is possible to assess gene expression differences in first trimester placentae from pregnancies with known outcomes, well before clinical disease symptoms or developmental abnormalities are apparent. [26][27][28][29][30][31][32] The results of this study correlate with our previous findings in which we have demonstrated a significant reduction in placental BGN from human pregnancies complicated by FGR collected at third trimester gestation compared with gestation-matched controls. 18 The results from this study support a temporal relationship between reduced BGN expression and SGA/FGR and, therefore, suggest a causal role for placental BGN in the success of pregnancy outcome.…”
Section: Discussionsupporting
confidence: 81%
“…Preeclampsia-specific altered gene expression has also been reported in chorionic villus samples obtained in early gestation from pre-symptomatic mothers who went on to develop preeclampsia [10], [11]. Furthermore, it has also been shown that alterations in expression patterns are not confined to the placenta and can be observed in circulating maternal white blood cell populations [12].…”
Section: Introductionmentioning
confidence: 90%
“…The sFlt-1/PlGF ratio has been proposed as an index of antiangiogenic activity that reflects alterations in both biomarkers and it is also a better predictor of PE than either measure alone [40]. A recent study utilized chorionic villous samples which were taken from pregnant women at 11 weeks of gestation, to develop an mRNA profile for those who were destined to become preeclamptic [41]. The authors suggested that alterations in IL-8, MMP-9, HLA-G and chemokine (CXC motif) ligand 10 were potentially useful for assessing risk, but that altered expressions of neurokinin B and HLA-C were the most predictive.…”
Section: Recent Developmentsmentioning
confidence: 99%